The art of public space : curating and re-imagining the ephemeral city - Gurney, Kim (Palgrave Macmillan, 2020)
Contents: Prelude, Johannesburg : Inside Out -- Overview, Nomadic Notions : Curating the Ephemeral -- Shoe Shop, Walking the Footloose City -- A MAZE. Interact, Playing the Cyborg City -- Spines, Performing the Spectral City -- Silobreaker, Art and The Uncertainty Principle -- Finale, Toward an Art of the Commons -- Bonus Track, Living the City : A View from End Street -- Afterword, Capturing Art in Common.